Evaluation Study on Fourteen Major Development Programmes in 33 Districts Affected by Left Wing Extremism(LWE) - Planning Commission (Planning Commission, 2010)
"Quick Evaluation Study on Major Development Programmes in 33 Districts affected by Left Wing Extremism The Task Force on the Left Wing Extremism (LWE) held on 23-12-2009 entrusted Programme Evaluation Organisation(PEO) of Planning Commission to conduct a quick evaluation study on major Development Programmes in 33 districts affected by LWE. The name of the Development Programmes and the 33 LWE districts along with the states to which they belong are given below in table A and B respectively Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) Pradhan Mantri Gram Sadak Yojana (PMGSY) Sarva Shiksha Abhiyan (SSA) Integrated Child Development Services (ICDS) Scheme Rajiv Gandhi Grameen Vidyutikaran Yojana(RGGVY) National Rural Health Mission(NRHM) Backward Regions Grant Fund (BRGF) Implementation of Scheduled Tribes and other Traditional Forest Dwellers (Recognition of Forest) Act, 2006. Ashram Schools and Hostels Rajiv Gandhi National Drinking Water Mission Targeted Public Distribution System Indira Awas Yojana Skill Development Programme e.g. ITIs, Polytechnics ,etc. State Level any Development/Welfare Programme especially for the .benefit of LWE districts."
"Programme Evaluation Organisation Planning Commission Government Of India New Delhi"